International pediatric thrombosis network to advance pediatric thrombosis research: Communication from the ISTH SSC subcommittee on pediatric and neonatal thrombosis and hemostasis. (31st March 2021) - van Ommen, C. Heleen; Albisetti, Manuela; Bhatt, Mohir; Bonduel, Marianne; Branchford, Brian; Chalmers, Elizabeth; Chan, Anthony; Goldenberg, Neil A.; Holzhauer, Susanne; Monagle, Paul; Nowak‐Göttl, Ulrike; Revel‐Vilk, Shoshana; et al.
Abstract: Pediatric thromboembolism is a rare and heterogenous disease. As a result, there is a paucity of knowledge with regard to natural history, management, and outcomes of most types of pediatric venous and arterial thromboembolism. International research collaboration is needed to fill these knowledge gaps. Not only randomized controlled trials, but also representative observational studies are required to answer all research questions. Therefore, the ISTH SSC Subcommittee on Pediatric and Neonatal Thrombosis and Hemostasis initiated the International Pediatric Thrombosis Network (IPTN). The aims of the IPTN include (1) development of the Throm‐PED registry to facilitate international prospective observational studies, and (2) establishment of a network of pediatric thrombosis centers experienced in effectively conducting clinical trials and observational studies. The IPTN needs dedicated clinicians all over the world and several funding sources to obtain high‐quality research data to reach its ultimate goal of improving care in children with thrombosis. The aim of this communication is to call for active participation in the IPTN to all physicians taking care of children with thrombosis worldwide.